2022
DOI: 10.1101/2022.11.26.518062
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Fungal antibiotics control bacterial community diversity in the cheese rind microbiome

Abstract: Potent antimicrobial metabolites are produced by filamentous fungi in pure lab cultures, but their ecological functions in nature are often unknown. Using an antibiotic-producing Penicillium isolate and the cheese rind microbial community, we demonstrate that a fungal specialized metabolite can regulate the diversity of bacterial communities. Inactivation of the global regulator, LaeA, resulted in the loss of antibacterial activity in the Penicillium isolate. Cheese rind bacterial communities assembled with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 87 publications
3
6
0
Order By: Relevance
“…The fungal metabolomes did not appear to change in any significant manner when they were co-cultured with either of the two bacterial partners. This strong metabolomic influence of fungi relative to bacteria in the cheese rind system is in agreement with several previous studies where fungi had stronger impacts on the system compared to bacteria 20,2835 . Pierce et al .…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The fungal metabolomes did not appear to change in any significant manner when they were co-cultured with either of the two bacterial partners. This strong metabolomic influence of fungi relative to bacteria in the cheese rind system is in agreement with several previous studies where fungi had stronger impacts on the system compared to bacteria 20,2835 . Pierce et al .…”
Section: Resultssupporting
confidence: 92%
“…A panel of bacterial-fungal pairwise co-cultures were profiled to detect and annotate specialized metabolites implicated in BFIs derived from the cheese rind microbiome. As previously noted, fungi are important members in natural and synthetic communities derived from the cheese rind microbiome, and the metabolomic data verifies the importance of fungi in complex cultures 19,28,29,35,64 . A variety of cultivation methods were tested which highlight the complexities of moving beyond monocultures, as Morin et al .…”
Section: Discussionsupporting
confidence: 69%
“…Three GCFs-dit, crm, and 6-were widely distributed across Ascomycota (Figure 4d). While these latter GCFs are not found in every lineage (Supplementary Figure S8), similar distributional patterns of the pseurotin gene cluster have recently been explained with vertical transmission -a pattern that emphasizes the potential importance of incomplete lineage sorting and gene loss even in SMs that often have strong ecological phenotypes (82). The latter three GCFs are widespread and account for 27.5% of all fungal ICS BGCs.…”
Section: The Distribution and Evolution Of Ics Gcfs In Fungisupporting
confidence: 62%
“…As previously noted, fungi are important members in natural and synthetic communities derived from the cheese rind microbiome, and the metabolomic data verifies the importance of fungi in complex cultures. 18,27,28,34,62 A variety of cultivation methods were tested which highlight the complexities of moving beyond monocultures, as Morin et al have previously used RB-TnSeq to show that pairwise interactions are not representative of interactions found in more complex community cocultures. 63,64 The complexity associated with expanding synthetic communities increases exponentially, requiring the optimization of methods that are able to accurately profile them.…”
Section: Discussionmentioning
confidence: 99%
“…This strong metabolomic influence of fungi relative to bacteria in the cheese rind system is in agreement with several previous studies where fungi had stronger impacts on the system compared to bacteria. 19,[27][28][29][30][31][32][33][34] Pierce et al found that bacterial fitness was impacted by fungal growing partners whereas statistical analysis of P. psychrophila JB418 and E. coli K12 metabolomic profiles were not fruitful because bacterial features were simply not present in co-culture feature lists. 20…”
Section: Fungal Metabolites Are Prominent Significant Features In Met...mentioning
confidence: 99%